The Brain of the Black (Diceros bicornis) and White (Ceratotherium simum) African Rhinoceroses: Morphology and Volumetrics from Magnetic Resonance Imaging - Bhagwandin, Adhil; Haagensen, Mark; Manger, Paul R. (Frontiers in Neuroanatomy, 2017)
The morphology and volumetrics of the understudied brains of two iconic large terrestrial African mammals: the black (Diceros bicornis) and white (Ceratotherium simum) rhinoceroses are described. The black rhinoceros is typically solitary whereas the white rhinoceros is social, and both are members of the Perissodactyl order. Here we provide descriptions of the surface of the brain of each rhinoceros. For both species, we use magnetic resonance images (MRI) to develop a description of the internal anatomy of the rhinoceros brain and to calculate the volume of the amygdala, cerebellum, corpus callosum, hippocampus and ventricular system as well as to determine the gyrencephalic index. The morphology of both black and white rhinoceros brains is very similar to each other, although certain minor differences, seemingly related to diet, were noted, and both brains evince the general anatomy of the mammalian brain. The rhinoceros brains display no obvious neuroanatomical specializations in comparison to other mammals previously studied. In addition, the volumetric analyses indicate that the size of the various regions of the rhinoceros brain measured, as well as the extent of gyrification, are what would be predicted for a mammal with their brain mass when compared allometrically to previously published data. We conclude that the brains of the black and white rhinoceros exhibit a typically mammalian organization at a superficial level, but histological studies may reveal specializations of interest in relation to rhinoceros behaviour.